Inspections Reforms : Do Models Exist? - Cordova-Novion, Cesar (International Finance Corporation, Washington, DC, 2016)
Analytical review of Inspections reforms in twenty five worldwide, with analysis of models and features of reforms undertaken. This paper provides a detailed look at the organizational and operational aspects of inspection reform and provides the basis for a substantive analysis of principles, commonalities and processes thereof. This paper attempts to standardize various approaches to inspection reform in a common framework. The paper identifies several models of organizational inspection reform and groups them into five general models/categories, applying a matrix approach to link this to the operational aspects of inspection reform. The paper features a detailed account of different models of inspection reforms in selected countries.